SOCIOLINGUISTICS AND FORENSIC LINGUISTICS : WHAT RELATIONSHIP ? - GUEBOUDJ Salah, BARECHE Khalissa & BOUREGBA Abla (Ziglôbitha)
Abstract:  Language is the world's soul; we live in a world shaped by language. This is why language is connected to all aspects of life and its issues. Language reveals a person's interests and inclinations, reflects their cultural level, and indicates their intellectual issues. It also reveals one's social identity and class or ethnic affiliation. Beyond this, language plays a role in crime, as it can be purely linguistic—such as insults, or threats—or a means of planning a crime, like luring someone before committing murder or using secret codes to smuggle weapons and drugs. Because of its presence in various criminal activities, a linguistic expert is necessary to help decipher criminal codes by studying and analyzing criminal discourse. This is the focus of our study titled "Forensic Linguistics and Sociolinguistics: What Relationship?". We aim to connect the nature and characteristics of these fields to understand their connections and highlight sociolinguistic principles that can be utilized in forensic linguistics.